(untitled) (Agora for Physical Education and Sport, 2018)
School football is an after-school activity of great educational and social relevance. A large number of children, accompanied by their families, participate in a competition in which they deposit illusions and expectations. Coordination emerges as an indispensable tool for addressing holistic child education, with special incidence in a stage of psychosocial changes. The children begin a parallel institutionalization in primary education and regulated sport. The study tries to understand the way in which actions are developed for the coordination between formal and extracurricular training spaces. An ethnographic case study is used in which participant observation is developed during a complete school year, complemented by in-depth interviews with teachers. The sample is composed of 101 six/seven years old schoolchildren (five girls and 96 boys), ten football coaches (all men, corresponding to ten different teams), 21 teachers (15 women and five men) and other actors such as families and organizers involved in the construction of the socio-educational scenario. The most relevant results show a sectorization of training activities for the child, that builds his learning in two parallel socio-educational contexts. The spaces that facilitate the communication are undertaken from personal initiatives of educational agents with presence in the two contexts. Relatives emerge as educational figures of relevance for coordination. The study concludes that communication is very important to provide a holistic education for the child in training and that extracurricular activities must be considered and used proactively for the pedagogical benefit of the particularities of each person.